Soil moisture, depth of water table and peat decomposition in Sadong Simunjan river basin, Sarawak using AIRSAR/TOPSAR data - Hashim, Mazlan; Busu, Ibrahim; Sim, Peter Hock Seng; Jong, Tieng Kong; Wan Kadir, Wan Hazli; Ngap, Dollah Salam (2002)
This study reports the operational implementation of technique for the exploitation of TOPSAR data in the framework of soil condition applications. Three empirical and theoretical radar backscatter models were examined in this study to characterize radar backscatter of TOPSAR data over coastal lowland of Sadong Simunjan River Basin, Sarawak, Malaysia. The main objective of this study is to analyze relationship between radar backscatter of TOPSAR data to (i) degree of wetness of drained peatland, (ii) depth of water table and, (iii) peat decomposition. The analysis of these models were examined using varying terrain-and-sensor related parameters namely surface roughness, dielectric constant, incidence angle, polarization and frequency, respectively. These simulated backscatters were used to understand the interaction of SAR with the above three methods before mapping the soil conditions using TOPSAR data. Results of this study indicate good relationship (RMSE<5.0) exists between radar backscatters and moisture content, even in the relatively moist drained peatland, which good correlationship with the depth of water table and peat decomposition at 0.89 and 0.88 respectively.